A Guide to Orthodontic Devices for Trainees in Orthognathic Surgery. Issue 3 (September 2022) - Girard, Alisa O.; Lake, Isabel V.; Chen, Jonlin; Dorfmann, Sabrina; Maduekwe, Uma; Lopez, Christopher D.; Ickow, Ilana; Yang, Robin
Purpose: Despite the interplay between orthodontics and orthognathic surgery, trainees in plastic surgery and oral and maxillofacial surgery do not receive formal training in orthodontics and associated hardware. This study aims to help surgical trainees better understand the role of orthodontic treatment in achieving enhanced dental occlusion and alignment and optimize surgical decision making. Methods: A review of recent literature was conducted to consolidate current practices for the use of orthodontic devices commonly used in orthognathic surgical patients. Results: Orthodontic treatments may be preventive, interceptive, and/or corrective. Braces and clear aligners are popular devices used to correct tooth positioning via 3 orders of control: first ("in-out" and rotation), second (mesio-distal angulation or "tip"), and third order (inclination or torque). Further, various treatments exist for skeletal and dental malocclusions, which may occur in transverse (crossbites, narrow arches) and/or sagittal (over/underbites) planes. Palatal expanders such as the Hyrax or Haas assist in correction of transverse deficiencies. Appliances for sagittal corrections typically take advantage of patient's remaining growth and include a variety of headgear types (cervical, high-pull, occipital, reverse-pull), functional appliances (fixed or removable), or simply the use of interdental elastics. Conclusion: As patients are increasingly seeking orthodontic care in conjunction with surgery, it is important for surgical trainees to develop a strong understanding of the various orthodontic devices used.